2018
DOI: 10.1111/acer.13854
|View full text |Cite
|
Sign up to set email alerts
|

Lower Prefrontal and Hippocampal Volume and Diffusion Tensor Imaging Differences Reflect Structural and Functional Abnormalities in Abstinent Individuals with Alcohol Use Disorder

Abstract: Findings showed specific structural brain abnormalities to be associated with visuospatial memory and problem-solving ability-related impairments observed in AUD. Higher RD in 6 WM regions suggests demyelination, and lower AD in left external capsule suggests axonal loss in AUD. The positive correlation between FA and age in bilateral putamen may reflect accumulation of iron depositions with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 99 publications
(122 reference statements)
4
42
0
Order By: Relevance
“…Alcohol use disorder (AUD) is a chronic, addictive, and relapsing disorder [1,2]. Individuals with chronic AUD manifest a variety of neurocognitive impairments [3], which may underlie both structural and functional features of the brain [4][5][6], and some of these impairments do not recover even after prolonged abstinence from drinking [7,8]. Recent studies have proposed the potential utility of resting state functional Magnetic Resonance Imaging (fMRI) connectivity as one of the neuroimaging biomarker for the quantitative clinical evaluation of AUD [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use disorder (AUD) is a chronic, addictive, and relapsing disorder [1,2]. Individuals with chronic AUD manifest a variety of neurocognitive impairments [3], which may underlie both structural and functional features of the brain [4][5][6], and some of these impairments do not recover even after prolonged abstinence from drinking [7,8]. Recent studies have proposed the potential utility of resting state functional Magnetic Resonance Imaging (fMRI) connectivity as one of the neuroimaging biomarker for the quantitative clinical evaluation of AUD [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this finding of hyperconnected hippocampal hub may suggest either a noisy communication across hippocampal sub-networks or an upregulated connectivity pattern representing overcompensation for the existing neural damage and memory impairments due to chronic drinking. In our earlier study using structural MRI, Pandey et al [16] reported smaller volume in several regions, including bilateral hippocampi, in AUD individuals compared to controls. Therefore, it is possible that damage to hippocampal connectivity to other regions of higher cortical functions (PFC, ACC, and LTC) may underlie cognitive impairments including memory deficits and blackouts that are common in chronic AUD patients [123][124][125][126].…”
Section: Parahippocampal Hyperconnectivity In Audmentioning
confidence: 69%
“…Therefore, it is possible that damage to hippocampal connectivity to other regions of higher cortical functions (PFC, ACC, and LTC) may underlie cognitive impairments including memory deficits and blackouts that are common in chronic AUD patients [123][124][125][126]. Interestingly, using the same sample AUD subjects, we reported reduced bilateral hippocampal volume which was also associated poor visual memory performance [16]. The finding that partly supports the current findings is from the only available eLORETA based FC study on AUD [59], where the authors reported theta band hyperconnectivity in hippocampal sub-networks among the dense connections in a small sample of craving, drug-resistant, relapsed AUD individuals (N = 11).…”
Section: Parahippocampal Hyperconnectivity In Audmentioning
confidence: 80%
See 2 more Smart Citations